J.M. Charcot correspondence - Charcot, J. M. (Jean Martin), 1825-1893.
ALsS from Charcot to Theodor Gomperz (circa 1884 and 1885 March 18), to the publishing firm Toeplitz & Deuticke (1891 August 1), and to two unidentified individuals (1892 January 8 and undated).
Neurologist.
Collection material in French.
Forms part of: Sigmund Freud collection.
Keywords: Gomperz, Theodor, -- 1832-1912 -- Correspondence; Toeplitz & Deuticke -- Correspondence; Neurologists